2021
DOI: 10.1038/s41418-021-00841-9
|View full text |Cite
|
Sign up to set email alerts
|

Lactate promotes macrophage HMGB1 lactylation, acetylation, and exosomal release in polymicrobial sepsis

Abstract: High circulating levels of lactate and high mobility group box-1 (HMGB1) are associated with the severity and mortality of sepsis. However, it is unclear whether lactate could promote HMGB1 release during sepsis. The present study demonstrated a novel role of lactate in HMGB1 lactylation and acetylation in macrophages during polymicrobial sepsis. We found that macrophages can uptake extracellular lactate via monocarboxylate transporters (MCTs) to promote HMGB1 lactylation via a p300/CBP-dependent mechanism. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
197
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(261 citation statements)
references
References 44 publications
7
197
2
Order By: Relevance
“…helps cancer cells escape immunity and has an inhibitory effect on immune killing (42)(43)(44)(45)(46). Following the first report of lactylation in Nature in 2019, a series of studies found that macrophages take up extracellular lactate to promote self-protein lactylation under both physiological and pathophysiological conditions (29,(47)(48)(49)(50), which further explains the immunological function of lactate at the molecular level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…helps cancer cells escape immunity and has an inhibitory effect on immune killing (42)(43)(44)(45)(46). Following the first report of lactylation in Nature in 2019, a series of studies found that macrophages take up extracellular lactate to promote self-protein lactylation under both physiological and pathophysiological conditions (29,(47)(48)(49)(50), which further explains the immunological function of lactate at the molecular level.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have revealed that lactylation may correlate with the release of inflammatory factors during sepsis ( 49 , 50 ). p300 (also known as KAT3B), a classic acetyltransferase that specifically acetylates histone H3K18 and H3K27 ( 30 ), also catalyses protein lactylation ( 29 ), and the study by Eskandarian et al found H3K18 acetylation to be significantly reduced during bacterial and adenovirus infection through SIRT2 and CBP/p300 ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…GPR81 has also been involved in the anti-inflammatory activity of lactate in mouse uterine inflammation during labor (161). It has recently been demonstrated in macrophages that lactate via GPR81/ ARRB2 increases acetylation of HMGB1 by inducing nuclear translocation of acetylase p300/CBP resulting in increased endothelium permeability (162).…”
Section: Lactate As a G Protein-coupled Receptor Agonistmentioning
confidence: 99%
“…Nuclear HMGB1 is ubiquitously expressed in the central nervous system including neurons, satellite cells, Schwann cells, microglia, and astrocytes, and the intracellular levels are further enhanced during traumatic neuropathy, denoting a possible link between HMGB1 release and nociception [20]. A programmed nuclear-cytoplasmic translocation of HMGB1 is a prerequisite in innate immune cells for active HMGB1 release via exocytosis of cytoplasmic vesicles such as secretory lysosomes [21] or via exosomal release during sepsis [22]. Studies by Merianda et al provided direct evidence that, in mice with sciatic nerve injury, HMGB1 located within DRGs shifts from cell bodies towards release [23].…”
Section: Hmgb1 Is Actively Released By Nociceptive Neuronsmentioning
confidence: 99%